Magnetic resonance imaging of the inferior alveolar nerve with special regard to metal artifact reduction. Issue 4 (April 2017) - Probst, Monika; Richter, Vivien; Weitz, Jochen; Kirschke, Jan Stefan; Ganter, Carl; Troeltzsch, Matthias; Nittka, Mathias; Cornelius, Carl-Peter; Zimmer, Claus; Probst, Florian Andreas
Abstract: Purpose: Magnetic resonance imaging (MRI) is an excellent imaging modality for displaying peripheral nerves. Since the knowledge about MRI of the inferior alveolar nerve (IAN) is limited, this pilot study aims to identify the prospects and limitations of MRI of the IAN, with special consideration of metal artifacts. Materials and methods: Initially, in vitro MRI of a dental implant was performed to establish an optimized protocol for metal artifact reduction using WARP sequences (a software package provided by Siemens Healthcare, Erlangen, Germany) including view angle tilting (VAT) and slice-encoding metal artifact correction (SEMAC) techniques. MRI with this optimized protocol was performed in three volunteers and four patients presenting with postoperative IAN impairment. Measuring the evaluable area and the artifact size was performed to assess the benefit of the specific artifact reduction sequences. Results: In vitro imaging of a dental implant demonstrated that WARP sequences with VAT and SEMAC techniques led to a volume reduction of the artifact of up to 69.1%. Observations in both volunteers and patients with neurosensory IAN impairment showed a distinct artifact reduction with the MRI protocol adapted to metallic materials. Additionally VAT and SEMAC techniques improved the imaging due to further artifact reduction. As a main drawback of the VAT technique, the image quality was compromised by a blurring effect. Still, on 3-T MRI the resolution was high enough to reveal even fine structures. Imaging of the IAN was successful in all cases despite metallic material in the region of interest, and structural IAN changes could be detected in correlation with clinical symptoms. Conclusion: In contrast to conventional radiography and computed tomography, MRI can directly depict the IAN and provide reliable information on its position and exact course within the mandible. MRI offers an objective assessment of IAN injuries, supporting the decision-making process regarding surgical exploration and microneural repair. With the advent of specialized MRI techniques such as VAT and SEMAC, reduction of metal artifacts is considerably improved.